Decision Support System for Students Final Project Title Acceptance at Ganesha Polytechnic Medan using Analytical Hierarchy Process (AHP) Method - Ramadhan, Wisnu; Wayahdi, M. Rhifky; Hasibuan, Eka Hayana (Journal of Technology and Computer, 2024)
Many students are confused about determining the title that has been standardized by the head of study program. Is the title they are proposing relatively easy and in accordance with what is standardized by the head of study program or could it actually make things difficult for the student? The decision making system method used is Analytical Hierarchy Process (AHP) with the criteria of level of difficulty, reference source, number of similar titles and reference accreditation. The manufacturing stages carried out in this research used the waterfall and web-based method. Making this application uses data processing procedures, Data Flow Diagrams and MySQL DBMS. The output of the research I have made is that it can make it easier for students to submit the title of their final assignment, making it easier for the head of study program to sort out whether the title that will be submitted by the student is in accordance with the standards set by the head of study program and can also assess at the same time whether the title is easy and suitable for use as a final assignment.